Editorial Vol1 no1 - Andrew Kendrick (Scottish Journal of Residential Child Care)
On behalf of the Scottish Institute for Residential Child Care (SIRCC) and the Advisory Board, I am delighted to be welcoming you to the first issue of the Scottish journal of Residential Child Care. We very much hope that you enjoy this new contribution to residential child care and find it useful and informative. The Scottish Institute for Residential Child Care was established on April 1st 2000. The aim of SIRCC is to ensure that residential child care staff throughout Scotland have access to the skills and knowledge they require to meet the needs of the children and young people in their care. The Scottish journal of Residential Child Care is one of the ways that we intend to achieve this aim.